Cr2N - Ag Thin Films - a Short Review - Jurči, Peter; Bílek, Pavel (Manufacturing Technology Journal, 2016)
The current paper summarizes briefly the results obtained by comprehensive investigations of magnetron sputtered Cr2N thin films with small additions of silver, whereas the pure Cr2N is used as a reference material. The main aspects reported here are: growth rate of the films, their growth manner, phase constitution, mechanical properties being represented by Young modulus and nanohardness, adhesion on the substrate made from Cr-V ledeburitic steel having a hardness of 60 HRC, tribological performance and effect on the mechanical properties of the substrate.
Keywords: Magnetron sputtering; Cr2N-Ag thin films; microstructure; mechanical properties; tribological performance